Self-compassion and Health Promotion Behaviors in Women with and without Type 2 Diabetes - Zhila Javadi Arzanagh; Anahita Khodabakhshi-Koolaee (Kerman University of Medical Sciences, 2019)
Self-compassion and Health Promotion Behaviors in Women with and without Type 2 Diabetes   Javadi Arzanagh Zhila1, Khodabakhshi-Koolaee Anahita2* 1. MSc in Counseling, Department of Counseling, Faculty of Human Science, Islamic Azad University, Science and Research of Tehran, Tehran, Iran 2. Assistant Professor, Department of Psychology and Education, Faculty of Humanities, Khatam University, Tehran, Iran * Corresponding Author: Anahita Khodabakhshi-Koolaee Address: No.30, Hakim Azam St., North Shiraz St., Mollasadra Ave., Tehran, Iran Tel: 00982189174119                                             Email: a.khodabakhshid@khatam.ac.ir Abstract: Background & Objectives: Type 2 diabetes is one of the most common metabolic diseases and is more common in women. There are many psychological and physical components involved in the prevention of type 2 diabetes, such as self-compassion and health-promoting behaviors. The present study was done to compare self-compassion and health promoting behaviors between women with and without type 2 diabetes. Methods: This descriptive- analytic study was carried out on 100 women with and 100 women without type 2 diabetes in Tehran/ Iran selected through convenience sampling in 2018. Data were collected using self-compassion and Walker's health promoting questionnaires. Data analysis was done using t-test and through SPSS22 software package. Results: According to the results, both self-compassion and health promoting behaviors showed significant difference in women with and without type 2 diabetes.  Conclusion: It is essential that diabetic patients follow behaviors such as healthy diet, regular exercise and body care to improve their physical health and to reduce depression and anxiety through self-compassion.   Keywords: Self-compassion, Health promotion behaviors, Diabetes type 2   Citation: Javadi Arzanagh Z, Khodabakhshi-Koolaee A. Self-compassion and Health Promotion Behaviors in Women with and without Type 2 Diabetes. Journal of Health Based Research 2019; 5(3): 235-45. [In Persian]